A Pragma-Semiotic Analysis of Emoji Usage in Facebook Anniversary Posts Across Generations - Abe, Precious Joan; Apitan, Richelle Anne; Ramos, Febbie Faith (Journal of Interdisciplinary Perspectives, 2025)
In today’s modern digital landscape, emojis have become a vital tool for expressing emotions and enhancing online communication. This study examines how various generational groups, specifically Generation X, Millennials, and Generation Z, utilize emojis in Facebook anniversary posts, highlighting the dynamic nature of digital expression across generations. The research aims to identify common patterns in the use of emojis, as well as their communicative functions, to recognize generational preferences and digital literacy. Using the qualitative pragma-semiotic approach, 60 Facebook posts were analyzed to examine the interaction between texts and emojis. Guided by Language Variation Theory and the Pragma-Semiotic Model of Communication, the study classified pragmatic functions, including tone modification, action representation, and aesthetic enhancement. Meanwhile, emojis served emotive, phatic, and decorative roles across generations. Findings reveal that while all generations use emojis to convey affection, humor, and cultural nuance, Gen Z expresses the most diverse and nuanced applications. Millennials balance emoji and text effectively, whereas Gen X tends toward minimal and straightforward usage. These generational variations underscore the role of emoji in shaping interpersonal and cultural communication. The study results suggest practical insights for educators across all levels, communicators, and digital users on the significance of emoji literacy for achieving effective online interaction and cultivating cross-generational understanding.